2020
DOI: 10.1016/j.heliyon.2020.e05523
|View full text |Cite
|
Sign up to set email alerts
|

Approximations for the inverse cumulative distribution function of the gamma distribution used in wireless communication

Abstract: The use of quantile functions of probability distributions whose cumulative distribution is intractable is often limited in Monte Carlo simulation, modeling, and random number generation. Gamma distribution is one of such distributions, and that has placed limitations on the use of gamma distribution in modeling fading channels and systems described by the gamma distribution. This is due to the inability to find a suitable closed-form expression for the inverse cumulative distribution function, commonly known … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Using the M-A method, Figure 3(a) shows the simulated magnitude probability distribution along with the observed one around the region of Taiwan (Figure 2). Compared to the observation, the two look like in good agreement, but actually the normalized differences (i.e., (observation -simulation)/observation) are quite substantial, in the range of -12% -35% as shown in Figure 3 Like the normal distribution that is commonly used in statistical and probabilistic studies, the gamma distribution has also been utilized in a variety of studies (e.g., Okagbue et al, 2020 [9]). For example, in medical science, it was found that the sum of basal and menstrual iron losses in women can be modeled by the gamma distribution satisfactorily (Yokoi, 2020 [10]).…”
Section: Introductionmentioning
confidence: 79%
“…Using the M-A method, Figure 3(a) shows the simulated magnitude probability distribution along with the observed one around the region of Taiwan (Figure 2). Compared to the observation, the two look like in good agreement, but actually the normalized differences (i.e., (observation -simulation)/observation) are quite substantial, in the range of -12% -35% as shown in Figure 3 Like the normal distribution that is commonly used in statistical and probabilistic studies, the gamma distribution has also been utilized in a variety of studies (e.g., Okagbue et al, 2020 [9]). For example, in medical science, it was found that the sum of basal and menstrual iron losses in women can be modeled by the gamma distribution satisfactorily (Yokoi, 2020 [10]).…”
Section: Introductionmentioning
confidence: 79%
“…In recent years, more researchers studied the applications of gamma distribution in statistical quality control, reliability, queuing theory, survival analysis, and communication engineering. For more details, refer to [43]. The present research is motivated by the idea of neutrosophic statistics given by [26] and extensive studies by Aslam from 2018 onwards on various neutrosophic and indeterminacy probability distributions in different sampling and control chart schemes; some citations are given in the introduction section.…”
Section: Introductionmentioning
confidence: 99%